Metagenomics Reveal Dynamic Coastal Ocean Reservoir of Antibiotic Resistance Genes - Stacy A. Suarez; Alyse A. Larkin; Melissa L. Brock; Allison R. Moreno; Adam J. Fagan; Adam C. Martiny (Journal of Marine Science and Engineering, 2025)
Exposure to antibiotic-resistant microbial communities in coastal waters is an important threat to human health. Through a ten-year coastal time series, we used metagenomics from 236 time points to provide a comprehensive understanding of the seawater resistome, temporal distribution, and factors influencing frequencies of specific resistance types. Here, we predicted that antibiotic resistance gene frequencies would increase during the winter due to increased rainfall, with terrestrial and enteric taxa serving as the primary carriers of resistance genes in coastal waters. We found that seasonal and interannual trends of antibiotic resistance genes vary by gene and the taxa carrying them, as opposed to a general increase in most resistance genes during specific seasons. However, we found that precipitation and Enterococcus levels may be accurate indicators for total antibiotic resistance gene levels in Newport Beach coastal water. Resistance genes were primarily carried by marine taxa, though some terrestrial taxa and opportunistic pathogens also harbored these genes. Non-marine taxa can be introduced through rain, human activity, or sewage spills. By using metagenomics, we were able to elucidate the antibiotic-resistant bacterial communities in Newport Beach coastal water and demonstrate both seasonal and multiannual trends in their abundance with important implications for local health and safety.